Maternal experiences of childhood psychological maltreatment: Relations with toddler emotional regulation. (June 2022) - Aviles, Ashleigh I.; Reisz, Samantha; Jacobvitz, Deborah; Hazen, Nancy
Childhood psychological maltreatment is a prevalent type of maltreatment, but one that is less studied compared to other forms of abuse. The intergenerational effects of psychological maltreatment have yet to be fully explored. This study examined mothers' recollections of childhood experiences of psychological maltreatment, assessed prenatally, and in relation to their own and their toddler's emotion regulation. Psychological maltreatment was assessed through a new coding system created for use with Adult Attachment Interviews (AAIs). Using structural equation modeling, we examined the direct effects of mothers' accounts of psychological and physical maltreatment during childhood on mothers' emotion dysregulation in a caregiving context and their toddlers' observed emotional dysregulation. Participants were 125 mother–toddler dyads in central Texas ( M age = 29.9 years). Mothers completed AAIs prenatally; toddlers completed frustration tasks to assess underregulation at 24 months of age. Maternal experiences of psychological maltreatment, but not physical maltreatment, were related to maternal emotion dysregulation during parenting and their children's emotional underregulation. Mother and child emotional dysregulation were also related. The effects of mothers' childhood experiences of psychological maltreatment have specific intergenerational consequences and must be explored separately from their experiences of physical maltreatment.